Assessing the naturalness of Malay emotional voice corpora - Mustafa, M.; Ainon, R.N.; Zainuddin, R.; Md Don, Z.; Knowles, G. (2011)
This research reports the development and evaluation of Malay emotional voice corpora through listening evaluation, and how the numbers of emotion choices offered to evaluators affect the result of the evaluation. The voice corpora comprises of three emotions, namely anger, sadness and happiness being expressed by two male and two female actors. The voice corpora were evaluated in two separate listening tests involving a number of Malay native evaluators balanced for gender, age and profession. In the first listening test, evaluators were given twenty five choices of emotions to choose from. For the second test, the number of emotion choices is only five. Each test was conducted separately with different group of evaluators. The results of the two tests are grossly different with the emotion identification rate of the first test lower than the second test.